Nursing of a case of severe pneumonia complicated with respiratory failure treated by mechanical ventilation (机械通气治疗1例重症肺炎合并呼吸衰竭患者的护理) - ZHANG Tingting (张婷婷); ZHOU Jie (周洁); WANG Jingjing (王晶晶); SHU Baozhen (舒宝珍) (Association of Integrative Nursing, 2021)
This paper reviewed the effective nursing interventions for a case of severe pneumonia complicated with respiratory failure treated by mechanical ventilation. A set of interventions including mechanical ventilation nursing, medication nursing, enteral nutrition support, catheter maintenance, skin care and psychological nursing were carried out, aiming to relieve the symptoms of respiratory failure, alleviate patient's condition and reduce the complications. (本文总结机械通气治疗1例重症肺炎合并呼吸衰竭患者的护理干预措施, 主要从机械通气护理、用药护理、肠内营养支持、管路护理、皮肤护理及心理护理等方面进行护理干预, 旨在改善患者呼吸衰竭状况和各项生命体征, 控制重症肺炎病情, 减少并发症的发生。)